Bactérias presentes nas mãos de profissionais de uma unidade neonatal antes e após a higienização das mãos com álcool em gel - Faria, Gabriel de Oliveira (2020)
Background: Health Care-Related Infections are a problem reported by hospitals around the world, increasing length of stay, costs and increase patient morbidity and mortality. In Neonatal Units, infections become an aggravating factor due to the conditions of their patients, the number of procedures performed and the frequency with which they are handled. In addition, the Hands of Health Professionals are one of the main ways of disseminating microorganisms in the hospital environment. Performs Hand Hygiene is extremely relevant for infection control. To increasing the adoption of Hand Hygiene, without losing it effectiveness Gel Alcohol use can be introduced. Aim: To evaluate the presence of bacteria in the hands of Health Professionals at a Neonatal Unit before and after Hand Hygiene with Gel Alcohol, as well as, to assess the susceptibility of isolated bacteria to antimicrobials. Method: The collections followed the principle of the modified “glove juice” technique, with samples before and after hand hygiene with gel alcohol in three different periods. Hand hygiene was performed without interference of the researchers. Bacteria found were identified by the MALDI-TOF system, and for samples after hygiene, susceptibility tests to antimicrobials were performed. Results: In total, 214 samples were obtained (before and after hand hygiene), of which 48.6% (n = 104) had bacterial growth before hygiene. After Hygiene, 24.3% (n = 52) samples were positive. From positive samples, 217 bacteria were isolated, the most frequent being coagulase-negative Staphylococcus in 27.2% (n = 41) before and 36.4% (n = 24) after, followed by Klebsiella pneumoniae 21.2% (n = 32) before and 24.2% (n = 16) after. Multidrug resistance to antimicrobials was found in 58.1% of Gram-Positive bacteria and Staphylococcus aureus (n = 4) 50% were resistant to Methicillin (MRSA), in Gram-Negative bacteria 34.3% were considered multidrug-resistant. Conclusion: There was a reduction in the number of bacteria after Hand Hygiene with Gel Alcohol, however, it was observed the permanence of microorganisms after this Hygiene, including multi-resistant ones, demonstrating a need for improvement in the Hygiene process.